Applying Social Practice Theory to Foster Mindful Consumption: A Case of Waste Banks in Indonesia - Putu Yani Pratiwi; Nosica Rizkalla; Tessa Handra; Eka Ardianto; Elliot Simangunsong (AIBPM Publisher, 2024)
Mindful consumption is an emerging research topic. The literature about mindful consumption is currently more focused on the individual. However, the more significant behavioral impact is collective behavior. So, the purpose of this research is to analyze how mindfulness instills changes in mindful consumption behavior at a collective level. This study applies social practice theory to explain how waste management as a social practice increases collective mindfulness and collective mindful consumption. This study applied a qualitative research design using a case study technique. A series of in-depth interviews were conducted with two waste banks and several households around them. The result of this study is waste management practice will evoke collective mindfulness and collective mindful consumption with the following processes: (1) Agents may reconfigure the elements of material, rules, and skills of waste management practices; (2) When agents perform the waste management practice frequently and consistently, the residents will participate in the practice which means that the new practice recruits new carriers; (3) For practice in the community to evolve, the recruitment of carriers depends on frequent exposure to the practice; and (4) When the residents are mindful, they will transform their product choices into solutions that benefit themselves and the environment. This study confirms that social practice may foster mindful consumption behavior at a collective level.